Development of LC3/GABARAP sensors containing a LIR and a hydrophobic domain to monitor autophagy. (20th March 2017) - Lee, You‐Kyung; Jun, Yong‐Woo; Choi, Ha‐Eun; Huh, Yang Hoon; Kaang, Bong‐Kiun; Jang, Deok‐Jin; Lee, Jin‐A
Abstract: Macroautophagy allows for bulk degradation of cytosolic components in lysosomes. Overexpression of GFP/RFP‐LC3/GABARAP is commonly used to monitor autophagosomes, a hallmark of autophagy, despite artifacts related to their overexpression. Here, we developed new sensors that detect endogenous LC3/GABARAP proteins at the autophagosome using an LC3‐interacting region (LIR) and a short hydrophobic domain (HyD). Among HyD‐LIR‐GFP sensors harboring LIR motifs of 34 known LC3‐binding proteins, HyD‐LIR(TP)‐GFP using the LIR motif from TP53INP2 allowed detection of all LC3/GABARAPs‐positive autophagosomes. However, HyD‐LIR(TP)‐GFP preferentially localized to GABARAP/GABARAPL1‐positive autophagosomes in a LIR‐dependent manner. In contrast, HyD‐LIR(Fy)‐GFP using the LIR motif from FYCO1 specifically detected LC3A/B‐positive autophagosomes. HyD‐LIR(TP)‐GFP and HyD‐LIR(Fy)‐GFP efficiently localized to autophagosomes in the presence of endogenous LC3/GABARAP levels and without affecting autophagic flux. Both sensors also efficiently localized to MitoTracker‐positive damaged mitochondria upon mitophagy induction. HyD‐LIR(TP)‐GFP allowed live‐imaging of dynamic autophagosomes upon autophagy induction. These novel autophagosome sensors can thus be widely used in autophagy research. Synopsis: Overexpression of fluorescently tagged Atg8/LC3 proteins to visualize autophagosomes can lead to artifacts; new peptide sensors have been developed that allow live‐imaging of endogenous LC3/GABARAP proteins at autophagosomes and at depolarized mitochondria. HyD‐LIR(TP)‐GFP detects all LC3/GABARAP‐positive autophagosomes, but gives the strongest signal for GABARAPL1‐positive autophagosomes. HyD‐LIR(TP)‐GFP allows live‐imaging of dynamic autophagosomes. HyD‐LIR(Fy)‐GFP specifically localizes to LC3A/B‐positive autophagosomes without affecting autophagic flux. HyD‐LIR(TP)‐GFP or HyD‐LIR(Fy)‐GFP efficiently colocalize with MitoTracker‐positive damaged mitochondria upon mitophagy induction. Abstract : Overexpression of fluorescently tagged Atg8/LC3 proteins to visualize autophagosomes can lead to artifacts; new peptide sensors have been developed that allow live‐imaging of endogenous LC3/GABARAP proteins at autophagosomes and at depolarized mitochondria.